Efficient treatment of digested piggery wastewater via an improved anoxic/aerobic process with Myriophyllum spicatum and bionic aquatic weed. (December 2021) - Zhang, Ze; Zhong, Mingjun; Sun, Yaping; Liang, Yuhai; Liu, Mengxue; Li, Jing; Cui, Hongcan; Meng, Fangang; Huang, Zhujian; Cui, Lihua
Graphical abstract: Highlights: A novel and efficient improved A/O system is proposed. The combining bionic aquatic weed and Myriophyllum sp . had a synergistic effect. The microbial community structure and metabolic pathways were changed. The thorny problem of NH4 + in digested piggery wastewater were effectively solved. Abstract: The traditional anoxic/aerobic process (A/O) process is widely used for treating digested piggery wastewater, but the lack of carbon sources leads to poor efficiency. Therefore, the process needs optimization to achieve high-efficiency and low-cost operation mode. In this study, an improved A/O system with bionic aquatic weed and Myriophyllum sp. was established to decontaminate digested piggery wastewater. The average removal efficiencies of chemical oxygen demand (COD), NH4 + -N, and total nitrogen (TN) by the improved A/O system was satisfactory. The average removal efficiencies of COD, NH4 + -N, and TN were 62.1%, 87.5%, and 61.9%, respectively. High-throughput sequencing identified a number of dominant microorganisms. The relative abundance of Nitrosomonas (ammonia-oxidizing bacteria) and Nitrospira (nitrite-oxidizing bacteria) was 0.07%–3.52% and 0.32%–1.30%, respectively. Combining bionic aquatic weed and Myriophyllum sp. altered the microbial community structure and metabolic pathways. The results demonstrate a cost-effective method for treating digested piggery wastewater.